The burden of T. solium cysticercosis and selected neuropsychiatric disorders in Mocuba district, Zambézia province, Mozambique. - Irene Langa; Fernando Padama; Noémia Nhancupe; Alberto Pondja; Delfina Hlashwayo; Lidia Gouveia; Dominik Stelzle; Clarissa Prazeres da Costa; Veronika Schmidt; Andrea S Winkler; Emília Virgínia Noormahomed (Public Library of Science (PLoS), 2022)
Background Taenia solium (neuro-)cysticercosis, a neglected tropical disease, can be associated with epileptic seizures and other neuropsychiatric (= neurological and psychiatric) disorders. This study aimed to evaluate the association of T. solium cysticercosis with selected neuropsychiatric disorders and/or symptoms (chronic headache, epileptic seizures/epilepsy and psychosis) in Mocuba district, Mozambique. Methodology Between March and May 2018, a cross-sectional study was conducted among 1,086 participants aged 2 years or above in Mocuba district, Zambézia province, central Mozambique, to assess the seroprevalence of human cysticercosis and risk factors for infection, as well as to explore its relation to selected neuropsychiatric disorders. Socio-demographic and clinical data were collected from each participant using a modified questionnaire designed by the Cysticercosis Working Group for Eastern and Southern Africa. Additionally, neuropsychiatric disorders, such as chronic headache, epileptic seizures/epilepsy and psychosis were assessed using four vignettes. T. solium antigen and cysticercosis IgG in serum were detected using both T. solium antigen B158/B60 enzyme linked immunosorbent assay (ELISA) and LDBIO Cysticercosis Western Blot, respectively. Principal findings Overall, 112/1,086 participants (10.3%) were sero-positive for T. solium antigen or antibodies. Prevalence of antibodies (6.6%; n = 72) was higher than of antigens (4.9%; n = 54). In the questionnaires, 530 (49.5%) of participants reported chronic headache, 293 (27%) had generalized epileptic seizures, 188 (18%) focal seizures and 183 (18.3%) psychosis. We found a statistically significant association between seropositivity for T. solium and chronic headache (p = 0.013). Additionally, increasing age (p = 0.03) was associated with Ag-ELISA seropositivity. Conclusions Our study revealed that in Mocuba, T. solium cysticercosis is prevalent and associated with self-reported chronic headache. Additionally, in the study setting, the seroprevalence of cysticercosis increased with age. However, it is not associated with other neuropsychiatric disorders such epileptic seizures/epilepsy and psychosis. Future studies are needed to confirm the high burden of neuropsychiatric disorders and their possible etiology, including neurocysticercosis, using additional serological, molecular biological and radiological diagnostic tools, as well as in-depth clinical examinations.